ESTIMASI EMISI DIOKSIN/FURAN DAN FAKTOR-FAKTOR YANG MEMPENGARUHI KONSENTRASI EMISI KE UDARA YANG BERASAL DARI INDUSTRI LOGAM - Lina Warlina; Erliza Noor; Akhmad Fauzi; Rudy C Tarumingkeng; Surjono H Sutjahjo (LPPM Universitas Terbuka, 2008)
Dioxin/furan is one of the persistent organic pollutants (POPs) that the government and public in Indonesia has not taken care of, as there is currently no policy on reducing dioxin/furan emission, even according to previous research dioxin/furan emission has already high. Steel industries produce dioxin/furan emission that will give negative impact to the people (cancer and death) and environment. The objective of this research was to estimate dioxin/furan emission and to determine factors that influence dioxin/furan emission concentration on the air, especially from steels industries. Methods employed in this research used emission factors to estimate dioxin/furan emission and Gaussian dispersion modeling to estimate emission concentration. The result showed that dioxin/furan emission is 9,38-13,54 gTEQ and it has to be reduced. Production is main factor to contribute dioxin/furan emission to the air. Besides that, emission concentration also depends on temperature, wind speed, height of stacks and radius from the site to the recipient. The conclusion of the research is dioxin/furan emission should be reduced, by means of first or second treatment.